1996
DOI: 10.1111/j.1479-828x.1996.tb02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Operative Laparoscopic Management of Adnexal Cysts: Initial Experience at the Royal Women's Hospital 1991–1994

Abstract: The introduction of operative laparoscopic surgery for benign adnexal cysts had led to shorter postoperative hospitalization (mean stay of 2.0 days) in association with a low rate of major complications (1.6%). A planned laparoscopic approach was successful in 95.2% (179/188) of patients. The majority of women were premenopausal (93.6%) and the most common procedure performed was an ovarian cystectomy (73.5% of cysts). Three ovarian cysts that were thought to be benign by preoperative and intraoperative assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…Study done by Yuen et al 7 showed that endometriosis and dermoid cysts were two most common benign ovarian tumour; ovarian conserving surgery was in 70% whereas in our study it was 58% and salpingooophorectomy in 22% which was less than other study. 3 The result of out study was also comparable with Parkar et al 11 where 73.5% had cystectomy, 17.4% had oophorectomy and 6% had aspiration.…”
Section: Discussionsupporting
confidence: 82%
“…Study done by Yuen et al 7 showed that endometriosis and dermoid cysts were two most common benign ovarian tumour; ovarian conserving surgery was in 70% whereas in our study it was 58% and salpingooophorectomy in 22% which was less than other study. 3 The result of out study was also comparable with Parkar et al 11 where 73.5% had cystectomy, 17.4% had oophorectomy and 6% had aspiration.…”
Section: Discussionsupporting
confidence: 82%
“…For therapeutic surgery, ovarian cyst (41.74%) was the most common followed by fibroid (24.05%) and adenomyosis (21.45%) ( Table 2). Yuen et al 8 and Parker et al 9 demonstrated in their study that planned laparoscopic approach was successful in 95.2% patients with ovarian masses. The most common therapeutic procedure done was laparoscopic hysterectomy in our study (44.06%) ( Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…Ten (5%) cases underwent oophorectomy.This contrasts with the study done by Shah et al 4 where endometriosis was the commonest ovarian pathology followed by dermoid cyst. Endometriosis and dermoid cysts were the twocommon benign ovarian tumors in their series of Yuen et al 8 Parker et al, 9 similarly commented that planned laparoscopic approach was successful in 95.2% and the most commonly performed surgery was laparoscopic cystectomy in 75.3% of cases. Yuen et al, 10 Parker et al, 9 and Yuen et al 8 concluded that operative laparoscopy should be the choice of treatment for benign adnexal masses.…”
Section: Discussionmentioning
confidence: 99%